Some Biographical Notes on Richard Bradock (and Others). (23rd December 2022) - Blayney, Peter W M
Abstract: Because the printer Richard Bradock began his apprenticeship during the five-year gap in the Stationers' early records, his origins have remained unknown. Tracing the life and career of his second known master (Henry Middleton), and of Middleton's own wider connections in the trade, has led to a record of a man who turns out to have been Bradock's father. Moreover, in his Stationers' Company Apprentices, 1605–1640 (1961), D. F. McKenzie wrongly supposed that some records of a Richard 'Bradde' (or 'Bradd', or 'Brad') were simply using an abbreviated form of 'Bradock'. Consequently, half the apprentices credited to Bradock should be reassigned to the Stationer Richard 'Brad', the son of Stationer John 'Bread' or 'Bred'.